ANOTHER COUNTRYSIDE? POLICY OPTIONS FOR LAND AND AGRARIAN REFORM IN SOUTH AFRICA/Ruth Hall (ed.) - Nabbie, Cadene (Scientia Militaria - South African Journal of Military Studies, 2013)
This study titled Another countryside? Policy options for land and agrarian reform in South Africa, edited by Ruth Hall, is significant given the challenges around diminishing global resources, including those affecting food security. Land reform does not only affect food security but also the maintenance of food production levels, development of small businesses, residential settlement and social cohesion. The focus on South Africa’s land and agrarian policies is relevant at a time when land issues have taken centre stage in public and private debates in South Africa. There are wide-ranging security implications for South Africa if the process of land reform is mismanaged. This study is a timeous one. Hall, as editor, contributes to some of the eleven chapters. The author is well versed in land issues in South Africa and her work focuses on the interests, actors and discourses which have shaped land reform processes in South Africa. As a background to this book, it would help to the read the 2010 study undertaken by Hall under the title The politics of land reform in post-apartheid South Africa, 1990–2004: A shifting terrain of power, actors and discourses.